2023
DOI: 10.3389/fmicb.2023.1121781
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization, pathogenicity screening, and molecular identification of Fusarium spp. isolates causing post-flowering stalk rot in maize

Abstract: Post flowering stalk rot (PFSR) of maize caused by the Fusarium species complex is a serious threat to maize production worldwide. The identification of Fusarium species causing PFSR based on morphology traditionally relies on a small set of phenomic characteristics with only minor morphological variations among distinct Fusarium species. Seventy-one isolates were collected from 40 sites in five agro-climatic zones of India to assess the diversity of Fusarium spp. associated with maize crops showing symptoms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
2
1
0
1
Order By: Relevance
“…This study, conducted in the North Central States of Nigeria identified 7 major fungi genera isolated from stored maize seeds ( Figure 1 ). The findings are consistent with previous studies conducted by Giorni et al, 15 Harish et al, 16 Katati et al, 17 and Price et al 3 which reported the presence of Fusarium, Aspergillus , and Penicillium as the primary genera isolated from maize grain. The growth of these isolated fungi is influenced by such factors as the temperature of storage and storage duration, and the degree of fungal contamination before storage, as well as insects and mites’ activities all have an impact on the development of these fungi.…”
Section: Discussionsupporting
confidence: 93%
“…This study, conducted in the North Central States of Nigeria identified 7 major fungi genera isolated from stored maize seeds ( Figure 1 ). The findings are consistent with previous studies conducted by Giorni et al, 15 Harish et al, 16 Katati et al, 17 and Price et al 3 which reported the presence of Fusarium, Aspergillus , and Penicillium as the primary genera isolated from maize grain. The growth of these isolated fungi is influenced by such factors as the temperature of storage and storage duration, and the degree of fungal contamination before storage, as well as insects and mites’ activities all have an impact on the development of these fungi.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the shape of their microconidia was mostly oval without septate, with length ranging from 1.917 mm to 9.277 mm. Our result was similar to that of pathogen characterization of post-flowering stalk rot in maize from agro-climatic zones of India, in which 71 isolates from four Fusarium species were identified (Harish et al, 2023). In addition, we found that the macroconidia from F. acuminatum were the largest with length up to 49.788 mm among our isolates.…”
Section: Discussionsupporting
confidence: 88%
“…Seleksi F1 mendapatkan 14 galur jagung berbiji ungu dengan daya hasil tinggi (Anirban, Hayward, et al 2023;Showkath Babu et al 2023). Seleksi F2 selanjutnya mendapatkan 9 galur jagung berbiji ungu yang berdaya hasil tinggi (Harish et al 2023). Jagung seleksi F3 dengan kriteria sempit pada karakter jumlah daun per tanaman, umur tanaman berbunga jantan, umur tanaman berbunga betina, dan umur panen .…”
Section: Pendahuluanunclassified